5'-Cholesteryl-phosphorothioate oligodeoxynucleotides: potent inhibition of methotrexate transport and antagonism of methotrexate toxicity in cells containing the reduced-folate carrier. - Henderson, G B (1995)
Polyanionic 5'-cholesteryl-phosphorothioate oligodeoxynucleotides of varying polymer length and nucleobase composition were examined for an effect on methotrexate transport via the reduced-folate carrier of L1210 mouse cells. Methotrexate transport was inhibited by each of the oligodeoxynucleotide analogs tested. Inhibition was most pronounced (IC50 = 0.21 microM, standard assay) for a 5'-cholesteryl heteropolymer consisting of 15 phosphorothioate deoxynucleotides with alternating deoxycytosine and deoxyadenosine (Chol-PS-d(CA)7C). Homopolymers with 15 deoxycytosine (Chol-PS-dC15) or deoxythymidine (Chol-PS-dT15) residues were approximately 2-fold less inhibitory than Chol-PS-d(CA)7C. The relative potency of transport inhibition by deoxycytosine oligomers of varying length was: Chol-PS-dC5 > Chol-PS-dC15 > Chol-PS-dC28 > Chol-PS-dC3. Substantial inhibition was retained in cells preincubated with inhibitors and washed prior to transport determinations and the inhibitor sensitivity could be increased substantially by reducing the concentration of cells. Mixed competitive and non-competitive inhibition was observed for each analog. In standard high-folate medium, Chol-PS-oligodeoxynucleotides (5.0 microM) had minimal effects on the growth of L1210 cells, but antagonized the cytotoxicity of methotrexate. The response to methotrexate (IC50 = 12 nM) decreased to the greatest extent (20.8-fold) in the presence of Chol-PS-d(CA)7C (IC50 = 250 nM). Under limiting folate conditions, Chol-PS-d(CA)7C alone inhibited cells growth by a process which could be reversed by folic acid. The results show that Chol-PS-oligodeoxynucleotides are among the most potent known inhibitors of the reduced-folate carrier. Direct growth inhibition of folate-deficient cells and antagonism of methotrexate cytotoxicity indicate that Chol-PS-oligodeoxynucleotides retain the ability to inhibit the reduced-folate carrier for several days in cultured cells.